Synthesis and Structural Characterization of (E)-N-(4-(Diethylamino)benzylidene)naphthalen-1-amine - Jian, Li (Asian Journal of Chemistry, 2011)
The compound (E)-N-(4-(diethylamino)benzylidene)naphthalen-1-amine (C21H22N2, Mr = 302.41) was synthesized and characterized by elemental analysis, IR spectra, 1H NMR spectra and single crystal X-ray diffraction. The crystal belongs to monoclinic, space group P21/c, with a = 24.517(2), b = 7.5266(8), c = 20.1621(19) Å, b = 109.9680(10)º, V = 3496.8(6) Å3, Z = 8, Dc = 1.149 g/ cm3, l = 0.71073 Å, μ(MoKa) = 0.067 mm-1, F(000) = 1296. The final refinement gave R = 0.0620, wR(F2) = 0.1374 for 6,145 observed reflections with I > 2s(I). X-Ray diffraction analysis reveals that the asymmetric unit of the title compound contains two independent molecules which adopt an E-configuration about the C=N double bond. The dihedral angles between the naphthalene ring and the benzene ring are 71.7 (2)º and 57.4 (2)º, respectively, in the two independent molecules.